2010
DOI: 10.1590/s0100-204x2010001100013
|View full text |Cite
|
Sign up to set email alerts
|

Chemical similarity among domesticated and wild genotypes of peanut based on n-alkanes profiles

Abstract: -The objective of this work was to analyze the epicuticular n-alkane profile of domesticated and wild peanut genotypes. Foliar epicuticular n-alkanes of four Arachis hypogaea genotypes and two wild species -A. monticola and A. stenosperma -were analyzed by gas chromatography. Chemical relationships between them were evaluated using the Dice coefficient and UPGMA method. Two clusters were formed: one with four A. hypogaea genotypes and the other with the two wild species. There is more similarity between the BR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The same group of compounds, were also identified in Arachis monticola Krapov. & Rigoni and A. stenosperma , through gas chromatography ( de Souza et al, 2010 ). In Brazil, another study showed that various wild species exhibited field resistance to E. flavens ( Michelotto et al, 2017 ).…”
Section: Role Of Peanut Wild Relatives For Resistancementioning
confidence: 99%
See 3 more Smart Citations
“…The same group of compounds, were also identified in Arachis monticola Krapov. & Rigoni and A. stenosperma , through gas chromatography ( de Souza et al, 2010 ). In Brazil, another study showed that various wild species exhibited field resistance to E. flavens ( Michelotto et al, 2017 ).…”
Section: Role Of Peanut Wild Relatives For Resistancementioning
confidence: 99%
“…In South America, besides Frankliniella sp. others such as Enneothrips flavens (Moulton) are commonly found on peanuts ( de Souza et al, 2010 ; Michelotto et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To obtain the cuticular wax, individual totally expanded whole fresh leaves from each species, with five replicates, underwent two successive washings during 30 s with 800 mL of dichloromethane (CH 2 Cl 2 ) (Souza et al 2010). n-alkane fractions were separated by TLC and analyzed by GC/EIMS (Shimadzu 17A, Kyoto, Japan).…”
mentioning
confidence: 99%